Dietary intake reports fidelity--fact or fiction? - Suchanek, Pavel; Poledne, Rudolf; Hubacek, Jaroslav A (Neuro endocrinology letters, 2011)
OBJECTIVES: Bias is common in the assessment of self-reported dietary intake and physical activity. Little is known about the reasons for this underreporting, which is obtained even from rural individuals and lean subjects. MATERIAL AND METHODS: Healthy volunteers (16 males, aged 18-55 years) were given two different full diets (high and low in saturated fat), each for a period of 4 weeks. RESULTS: The subjects were able to provide a report of their dietary intake with relatively high accuracy (68.4%) on day one. Accuracy declined on day two (64.2%), and on day three, the reporting accuracy was only 55.0% (p<0.05). Interestingly, on day one, individuals were more precise (p<0.05) in their dietary reports if they had consumed an unhealthy diet high in saturated fat (72.5%) than a healthy diet high in unsaturated fat (64.4%). The most frequently omitted items were fruits and vegetables. The non-reporting of food items consumed is very high, even in the short term, and individuals tend to remember unhealthy items better. CONCLUSIONS: Our pilot study showed that the inaccuracy of self-reported data includes not only the underestimation of energy intake (portion size) but also inaccurate qualitative data.
Keywords: dospělí; Eating; mastné kyseliny; Vegetables; energetický příjem; Adult; Fatty Acids; mladý dospělý; zelenina; Adolescent; Reproducibility of Results; Diet Surveys; lidé; Energy Intake; Fruit; zkreslení výsledků (epidemiologie); přijímání potravy; dieta; ovoce; Bias; reprodukovatelnost výsledků; venkovské obyvatelstvo; Diet; Male; dieta - přehledy; Young Adult; lidé středního věku; mužské pohlaví; Middle Aged; mladiství; Rural Population; Humans